Characteristics and properties of natural hydroxyapatite derived from bovine bone for biomedical applications / Aliasghar Niakan - Aliasghar , Niakan (2016)
Bovine bone is a hierarchically structured natural composite material, consisting of collagen as an organic phase, hydroxyapatite as a mineral phase, and hydroxyl. The aim of this research is to study the properties of natural hydroxyapatite (HA) developed from bovine bone. Sintering process was used to transform the bovine bone constituents into pure HA mineral phase which makes bovine bone such a unique biological material. Femur cortical bone was harvested from local slaughterhouse, cleaned and subsequently sintered in air atmosphere at different temperatures ranging from 200ºC to 1300ºC with heating ramp rate of 10ºC for 2 hours. The samples were characterised through bulk density measurement, X-ray diffraction, Micro X-ray Fluorescence, Fourier transforms infrared spectroscopy analysis, simultaneous thermal analyser, differential scanning calorimeter, Vickers hardness and fracture toughness determination. In addition, the microstructural evolutions of the sintered bodies were also examined by field emission scanning electron microscopy and transmission electron microscopy. The results revealed that the thermal stability of the HA matrix was not disrupted and that all of the sintered samples exhibited phase pure HA. Nevertheless, sintering at 750ºC was identified as the optimum temperature to produce a well-defined porous HA body with a relative density of 50% and Vickers hardness of 172 MPa. In addition, a natural interconnected porous structure was clearly visible, and the pores were distributed homogeneously throughout the matrix. Uniform pores with a mean size of approximately 152 nm and HA grains sizes ranging from 111 nm to 248 nm were obtained. Finally, biocompatibility of the bovine-derived samples was evaluated via in vitro human osteocalcine cells test. Cell viability and cell attachment were undertaken by human bone marrow stem cell. The results of cell viability, cell attachment and osteocalcine test on sintered samples indicated minor cytotoxic response. Thus, this research proved that natural hydroxyapatite developed from sintered bovine bone could be a suitable bioceramic for use in clinical application.